THE IMPACT OF MOTIVATION CLASSES ON SELF-AWARENESS AND THE REINFORCEMENT OF LIFE VALUES - Djoko Supriatno; Prima Crismono; Muhammad Ilyas; Achmad Faisol; Elga Yanuardianto (Universitas Muhammadiyah Jember, 2025)
This study aims to examine the impact of motivation classes on enhancing participants’ self-awareness and reinforcing their life values. Utilizing a quantitative approach with a pre-test and post-test experimental design, the study involved 186 respondents who participated in the motivation classes. The instrument used was a closed-ended questionnaire with a 1-4 Likert scale, measuring the two main variables. The Wilcoxon Signed Rank Test results showed significant differences in both variables, with a p-value of 0.000 for self-awareness and reinforcement of life values, indicating that the motivation classes had a positive effect on improving self-awareness and strengthening life values. Furthermore, the results of the Spearman's Rank Correlation analysis revealed a significant positive correlation between increased self-awareness and reinforcement of life values (r = 0.62, p = 0.000). These findings support the theory that enhanced self-awareness is associated with strengthened life values, which in turn can improve individuals’ psychological well-being. Overall, the study concludes that motivation classes can serve as an effective means of personal development, positively impacting self-awareness and life values, and contributing to individual well-being.